What happens before, during and after crisis for someone with dementia living at home: A systematic review. (February 2021) - Hopkinson, Jane B; King, Amanda; Mullins, Jane; Young, Lucy; Kumar, Sugandha; Hydon, Kate; Muthukrishnan, Sabarigirivasan; Elliott, Fiona; Hopkinson, Martin
Background: People living with dementia often experience crisis. Home treatment of crisis is an alternative to hospital admission that can have better outcomes. This systematic review is about people with dementia living at home and in crisis. It identifies modifiable factors in the crisis process that may facilitate crisis resolution. Methods: The protocol is registered on PROSPERO. A systematic search of MEDLINE, EMBASE, CINAHL, AHMED, PsycINFO, Cochrane Library and references of retrieved publications, identified empirical research in English language and date range January 2000 to February 2019. Two researchers independently screened abstracts, selected publications and extracted data using a framework based on published guidelines. This is a report of the analysis and narrative synthesis. Results: The search identified 2755 titles and abstracts, 76 were selected for full-text examination and 13 agreed for inclusion. The included studies evidence that: for a person with dementia, crisis is a process that begins with a problem judged to put them or others at risk of harm. It leads to decision and action to treat this risk, thus resolve the crisis. Such crisis can be predicted or unpredicted and progress quickly or slowly. Medical treatment, community resources and psychosocial support of personal resources, decision making, relationships and social networks, are all modifiable factors that can treat the risk of harm during crisis. Carers' and professionals' knowledge and skills in dementia care are likely to play a key role in crisis resolution in the home. Conclusion: There has been limited investigation of the process and management of crisis at home for people living with dementia. The results of this review provide a foundation for future research. There is no consensus on critical components of home treatment to facilitate crisis resolution. However, education in dementia care for carers and professionals is likely to prove essential to successful home treatment.